Pulau Perak exploring a marine treasure-trove - Izham Yusoff 1967-; Anuar Abdullah (Institut Terjemahan & Buku Malaysia Berhad, 2015)
Bina Darulaman Berhad proposed the idea of exploring and conducting a preliminary assessment of a little-known geographical area in Kedah known as Pulau Perak for the purpose if ascertaining its biological diversity and potential for development. Prior to the expedition, four broad objectives were outlined and set up as the basis for exploration of the waters surrounding Pulau Perak: To conduct a structured exploration of Pulau Perak and document the processes used the findings obeserved. To identify new venues for local industry. To ascertain the vialibitlity of Pulau Perak as a new diving location to relieve "over diving" at the popular destinations. To develop Pulau Perak as a model for an eco-travel destination that is supported by proper research